2019
DOI: 10.2478/s11756-018-00189-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete mitochondrial genome of Rhinogobius leavelli (Perciformes: Gobiidae: Gobionellinae) and its phylogenetic analysis for Gobionellinae

Abstract: Freshwater Gobionellinae fish Rhinogobius leavelli is a common small-bodied species, distributed in eastern Asia. Information about genetic characteristics of Rhinogobius fish had been published only for five species, and there were still no relevant reports on R. leavelli. In the present study, the complete mitochondrial genome of R. leavelli was determined, which was 16,499 bp in length with A + T content of 52.5%, consisting of 13 protein-coding genes, 2 ribosomal RNAs, 22 tRNAs, and a control region. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“… 2020 ), R. cliffordpopei (Wang et al. 2019 ), R. leavelli (Zhang and Shen 2019 ), R. rubromaculatus ) formed Clade B. Furthermore, R. filamentosus clustered with R. duospilus , and they formed a sister-group relationship with the other ten Rhinogobius species.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“… 2020 ), R. cliffordpopei (Wang et al. 2019 ), R. leavelli (Zhang and Shen 2019 ), R. rubromaculatus ) formed Clade B. Furthermore, R. filamentosus clustered with R. duospilus , and they formed a sister-group relationship with the other ten Rhinogobius species.…”
Section: Resultsmentioning
confidence: 96%
“… 2018 ; Chen et al. 2019 ; Zhang and Shen 2019 ), there were still no relevant reports on the genetic characteristics and phylogenetic position of R. filamentosus . This research aimed to sequence the complete mitogenome of R. filamentosus, provide fundamental molecular data for evolution, and determine its phylogenetic placement in the genus Rhinogobius .…”
Section: Introductionmentioning
confidence: 99%
“…sequencing data were used for mitochondrial genome assembly for each sample. We performed molecular phylogenetic analyses of our aligned mitochondrial genomes along with mitochondrial genome sequences of R. cliffordpopei (Nichols), R. duospilus (Herre), and R. leavelli (Herre) from the International Nucleotide Sequence Database published by Tan et al (2020), Wang et al (2019), and Zhang & Shen (2019), using the GTR+I+Gamma model, and performed a maximum likelihood (ML) analysis using RAxML version 8.2.3 (Stamatakis, 2014) Diagnosis. Pectoral fin with 14-16 rays (usually 15 rays).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, artificial breeding of this fish species has been successful and artificial cultivation has been carried out in some areas of Yunnan Province, China. Mitochondrial genome can provide sufficient resources for genome-wide evolutionary studies and has demonstrated the potential to resolve phylogenetic relationships at different taxonomic levels, and understand the structure and functional evolution (Zhang and Shen 2019 ; Shen et al. 2020 ; Yang et al.…”
mentioning
confidence: 99%